Badanie ocznego przepływu krwi w jaskrze – możliwości i bariery - Wierzbowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
Patients with glaucoma demonstrate disturbed ocular blood flow that is induced by oxidative stress, endothelial dysfunction and impaired autonomic nervous system activity. It has not yet been clarified whether the reduced blood flow in glaucoma is secondary (to tissue loss or a decrease in perfusion pressure with disturbed autoregulation) or is itself the primary cause of optic neuropathy. Due to the complex system of blood supply to the optic disc and retina there is no single diagnostic method that allows the measurement of all vascular beds in the eye important for glaucoma. The article, based on a review of the literature, discusses current and previous techniques for assessing retinal, choroidal and retrobulbar circulation in glaucoma, with particular attention to color Doppler ultrasonography and optical coherence tomography angiography. Advantages and limitations of each technology are presented and the results of the most important research with their use are listed. In the light of the latest research, optical coherence tomography angiography is an imaging modality that has great scientific and clinical potential to enhance the knowledge of glaucoma pathogenesis and to improve the ability to detect glaucomatous damage.